Sequencing and Characterisation of Complete Mitogenome DNA for Rasbora hobelmani (Cyprinidae) with Phylogenetic Consideration - Chung, Hung Hui; Lim, Leonard Whye Kit; Kamar, C. K. A.; Liao, Y.; Lam, T. T.; Chong, Y. L. (Pleiades Publishing, Ltd., 2020)
The Kottelat rasbora Rasbora hobelmani is a small ray-finned fish categorized under the genus Rasbora in the Cyprinidae family. In this study, the complete mitogenome sequence of R. hobelmani was sequenced using two pairs of primers covering overlapping regions. The mitogenome is 16541 bp in length, housing 22 transfer RNA genes, 13 protein-coding genes, two ribosomal RNA genes and one putative control region. Identical gene organisation was spotted between this species and other Rasbora genus members. The heavy strand contains 28 genes while the light strand contains the remaining nine genes. Most protein-coding genes employ ATG as start codon, except for the COI gene, which exploits GTG instead. The central conserved sequence blocks (CSB-F, CSB-E and CSB-D), variable sequence blocks (CSB-3, CSB-2 and CSB-1) as well as the terminal associated sequence (TAS) are conserved in the control region. The maximum likelihood phylogenetic tree revealed the close phylogeny of R. hobelmani with R. sumatrana, R. aprotaenia, R. lateristriata and R. steineri with bootstrap value of at least 99%. This work acts as milestone towards future evolution and population genetics studies of this species as well as the Rasbora genus.